Fear of COVID 19 Infection Across Different Cohorts: A Scoping Review - Quadros, Shalini; Garg, Shalini; Ranjan, Rupesh; Vijayasarathi, Guruprasad; Mamun, Mohammed A. (Frontiers in Psychiatry, 2021)
Background: Psychological stressors like panic, fear, phobia, etc., are substantially reported during the COVID–19 outbreak. In the prior outbreaks, fear of being infected was reported as the prominent suicide stressors. Therefore, fear of infection has become a concern in the context of the COVID–19 pandemic because it worsens emotion, cognition, and behavioral responses. Understanding the extent of fear of COVID-19 infection in various cohorts would aid in gauging the mental health services, which was a remedy in the present review. Methods: Adhering to Arksey and O'Malley’s framework for conducting a scoping review, a systematic search was performed in the month of September 2020 in several databases, including Scopus, PubMed, Web of Science, etc. Considering the inclusion criteria, a total of 14 articles were included in the present review. Results: All of the included studies were conducted via online platforms, whereas all but one studies were cross-sectional in nature (including a mixed-method study, and a comparative study). Most of the studies were conducted among the general population (n=12), within March and May 2020 (n=9), from Asian countries (n=7), and considered a self-developed item for fear of COVID-19 assessment (n=8; whereas the Fear of COVID-19 Scale was used in 6-studies). The prevalence of fear of COVID-19 was reported to be 18.1% to 45.2%, although no cutoff point or criteria was mentioned for such a prevalence estimation of the Fear of COVID-19 Scale. However, females, younger adults, urban residents, divorcees, healthcare workers, being in quarantine settings, suspicion of being infected, having mental health problems, etc., were found being at an increased risk of COVID-19 fear. Conclusions: Being one of the first reviews to this context, the findings are anticipated to be helpful to verdict the possible solutions for reducing fear of COVID-19 and facilitate further studies on strategies how to alleviate such a stressful situation.